Circumstantial indications as potential signs of the construction of concepts related to animal experimentation in scientific education (Práxis Educativa, 2017)
The work problematizes the theme animal expeimentation with students (S=14) of Biological Sciences in a public university of the State of Paraná, Brasil. The work is based based on the Semiology of Messages and Signs by Prieto (1973), and brings the analysis of information collected in a didactitc unity on the theme. The objective of the research was to evaluate the role of circumstantial indications in the construction of concepts related to animal experimentation. It demonstrates the circumstantial indications can be signs used by the teacher with the purpose not only to clarify the discourse and reduce ambiguities, but also to provoke the students' reflective thinking. Keywords:  Circumstantial Indications. Prieto’s Semiology. Animal Experimentation.